2016
DOI: 10.1590/1983-1447.2016.02.58131
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição do brinquedo terapêutico estruturado em um modelo de cuidado de enfermagem para crianças hospitalizadas

Abstract: Objective To analyse how therapeutic play structured in a nursing care model contributes to the care of hospitalised children. Method This is a qualitative study based on convergent care research (CCR). Seven children participated in the study. Data were collected in September and October of 2014 by means of interviews with open-end questions and participant observation of therapeutic and dramatic play sessions and/or instructional play sessions based on the stages "Welcoming/Playing/Concluding" of the nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
60

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 9 publications
0
21
0
60
Order By: Relevance
“…(14) Através dele percebe-se que a criança compreende a necessidade da internação e pode vivenciar este momento de forma mais tranquila. (2) Durante as dramatizações, percebeu-se que as crianças estavam familiarizadas com os materiais utilizados na punção venosa. Apesar de não saberem os nomes dos componentes utilizados, a demonstração da técnica foi realizada de forma similar à do enfermeiro, não havendo necessidade, por exemplo, de auxiliar em relação ao manuseio dos dispositivos agulhados e da aspiração da solução fisiológica.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…(14) Através dele percebe-se que a criança compreende a necessidade da internação e pode vivenciar este momento de forma mais tranquila. (2) Durante as dramatizações, percebeu-se que as crianças estavam familiarizadas com os materiais utilizados na punção venosa. Apesar de não saberem os nomes dos componentes utilizados, a demonstração da técnica foi realizada de forma similar à do enfermeiro, não havendo necessidade, por exemplo, de auxiliar em relação ao manuseio dos dispositivos agulhados e da aspiração da solução fisiológica.…”
Section: Discussionunclassified
“…Assim sendo, através da brincadeira, o sofrimento passivo torna-se um domínio ativo e os episódios traumáticos podem ser melhor dominados. (2,15) Autores evidenciam a importância da aplicação desse instrumento para tornar a criança mais cooperativa com a equipe de enfermagem. Antes as crianças mostravam-se inquietas e chorosas, e após o emprego do brinquedo terapêutico elas interagiram melhor com as enfermeiras.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is suggested, as another activity that can be used by nurses, the creative therapy with art (CTA), which involves three techniques: music therapy; dance/movement therapy and art therapy, through drawings, 28 in addition to the therapeutic toy. 10 It is argued that the research findings indicated a variety of moments in which play strategies are used during the hospitalization of the child, highlighting their majority applicability during care / procedures. It is important to emphasize that play strategies should be used in any care situation at any time of hospitalization, since the response is positive and satisfactory, both regarding the behavior of the child and the performance of the procedure during nursing care.…”
Section: Here We Have a Space [Toy Library] Which I Particularly Almentioning
confidence: 95%
“…8 It can be observed that in the range of possibilities of play strategies with hospitalized children are games, relaxation, dialogue, music, paintings and storytelling, 9 besides the therapeutic toy, which is a structured toy which helps in reducing the anxiety of the child coming from threatening and atypical situations, as in invasive and painful procedures. 10 It is suggested that play strategies need to be part of Nursing care with the child who experiences a hospitalization, too, from the perspective of a right to be guaranteed. It is emphasized that, according to the UN Declaration of the Rights of the Child, the need to play is seen as essential for the child.…”
mentioning
confidence: 99%